Status Hak Asuh Anak akibat Perceraian dalam Perkawinan Campuran - Putu Sandiawan Putra Wiranata; Ida Ayu Putu Widiati; Ni Made Puspasutari Ujianti (Warmadewa Press, 2025)
Many Indonesian citizens are now married to foreigners. The marriage has legal consequences in the event of divorce, including the status of custody due to the divorce of the marriage. From the above background, the author took the research title: Situation of child custody due to divorce in mixed marriages. The research question is about the regulation of children's rights in mixed marriages and the status of custody in the event of divorce in a mixed marriage. The research method used is normative legal research method. Conceptual and legislative approaches. The results show that there is no general difference between the rights of children from mixed marriages and the rights enjoyed by children from other normal marriages. Only children from interracial marriages have special rights: the right to choose their nationality and to have parental rights when they turn 18. In the event of divorce, with due regard to the best interest of the child.